Prescribing practices and clinical predictors of glucose‐lowering therapy within the first year in people with newly diagnosed Type 2 diabetes. Issue 12 (3rd July 2015) - Mor, A.; Berencsi, K.; Svensson, E.; Rungby, J.; Nielsen, J. S.; Friborg, S.; Brandslund, I.; Christiansen, J. S.; Vaag, A.; Beck‐Nielsen, H.; Sørensen, H. T.; Thomsen, R. W.
Abstract: Aim: To examine prescribing practices and predictors of glucose‐lowering therapy within the first year following diagnosis of Type 2 diabetes mellitus in a clinical care setting. Methods: We followed people enrolled in the Danish Centre for Strategic Research in Type 2 Diabetes (DD2) cohort from outpatient hospital clinics and general practices throughout Denmark in 2010–2013. We used Poisson regression to compute age‐ and gender‐adjusted risk ratios (RRs). Results: Among 1158 new Type 2 diabetes mellitus patients, 302 (26%) did not receive glucose‐lowering therapy within the first year, 723 (62%) received monotherapy [685 (95%) with metformin], and 133 (12%) received more than one drug. Predictors of receiving any vs. no therapy and combination vs. monotherapy were: age < 40 years [RR: 1.29 (95% CI: 1.16–1.44) and 3.60 (95% CI: 2.36–5.50)]; high Charlson Comorbidity Index [RRs: 1.20 (95% CI: 1.05–1.38) and 2.08 (95% CI: 1.16–3.72)]; central obesity [RRs: 1.23 (95% CI: 1.04–1.44) and 1.93 (95% CI: 0.76–4.94)]; fasting blood glucose of ≥ 7.5 mmol/l [RRs: 1.25 (95% CI: 1.10–1.42) and 1.94 (95% CI: 1.02–3.71)]; and HbA1c  ≥ 59 mmol/mol (≥ 7.5%) [RR: 1.26 (95% CI: 1.20–1.32) and 2.86 (95% CI: 1.97–4.14)]. Weight gain ≥ 30 kg since age 20, lack of physical exercise and C–peptide of < 300 pmol/l also predicted therapy. Conclusions: Comorbidity, young age, central obesity and poor baseline glycaemic control are important predictors of therapy one year after Type 2 diabetes mellitus debut. What's new?: This nationwide prospective cohort study describes real‐life prescribing practices and predictors of glucose‐lowering therapy within the first year following Type 2 diabetes mellitus diagnosis in Denmark. Within one year after diabetes debut, 74% of patients were on a glucose‐lowering drug, and 12% received combination therapy. Presence of comorbidity, young age, central obesity and poor baseline glucose control were important predictors, both of receiving any glucose‐lowering therapy and of receiving combination therapy.